Accessing justice in Kenya: An analysis of case backlog in Nakuru environment and land court - Onserio, Michelle Nyaboke (Strathmore University, 2020)
In Kenya, various laws such as the Constitution and Judicial Service Commission Act of 2015, guarantee the right to access to justice as a human right. However, evidence shows that people are not accessing justice expeditiously due to case backlog. This problem arises from several factors ranging from problems in the judiciary’s administrative system to the attitude of judicial officers. An attempt to solve the problem has been the transformation framework put in place by the Judiciary to increase judicial staff and the number of courts. Despite this measure, the problem persists in various jurisdictions. This study seeks to examine factors contributing to the persistence. The research focuses on the Environment and Land Court in Nakuru for the period between 2012- 2018 where the framework has not been implemented yet. The interest of study in the Environment and Land Court is determined by the fact that the Kenya National Bureau of Statistics has ranked it among the courts with the highest case backlog. Moreover, the research assesses how this phenomenon limits the right of access to justice. For the purpose of this analysis, the study uses the Human rights theory from the perspective of legal rights theory. In this regard, the research methodology adopted is the descriptive design approach which entails collecting information sought out from selected respondents by carrying out interviews and/or questionnaires. The study showed that the reforms suggested in the judiciary transformation framework have not been implemented in its entirety therefore creating a backlog problem.
A dissertation submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree